2019
DOI: 10.1111/opec.12166
|View full text |Cite
|
Sign up to set email alerts
|

Predicting United Arab Emirates' real effective exchange rates using oil prices

Abstract: We examine whether oil prices help produce accurate forecasts of the real broad effective exchange rate of the United Arab Emirates (UAE). Using monthly data for 1994–1999, we formulate a univariate moving average (MA) and an augmented moving average (A‐MA) model to generate multi‐period forecasts of UAE real exchange rates for 2000–2019. The MA model utilises past information in real exchange rates, while the A‐MA model utilises past information in both real exchange rates and oil prices. Our results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…While there are fewer studies about the real effective exchange rate's impact on real estate price. Baghestani (2019) [12] developed A-MA model to predict the real effective exchange rate of the UAE using monthly data of oil prices from 1994-2009, while the changes in the real effective exchange rate of the UAE were derived by a non-parametric approach based on the data from 2009-2019. Alleyne (2020) developed a disaggregated data demand model, focusing on the impact of the real effective exchange rate on tourism demand.…”
Section: Review Of Literaturementioning
confidence: 99%
“…While there are fewer studies about the real effective exchange rate's impact on real estate price. Baghestani (2019) [12] developed A-MA model to predict the real effective exchange rate of the UAE using monthly data of oil prices from 1994-2009, while the changes in the real effective exchange rate of the UAE were derived by a non-parametric approach based on the data from 2009-2019. Alleyne (2020) developed a disaggregated data demand model, focusing on the impact of the real effective exchange rate on tourism demand.…”
Section: Review Of Literaturementioning
confidence: 99%
“…According to the wealth channel, when oil prices increase, wealth is transferred from oil‐importing countries to oil‐exporting countries, and, therefore, currencies of oil‐exporting (importing) countries appreciate (depreciate) through current account imbalances and portfolio reallocation (Beckmann and Czudaj, 2013). Empirical studies have generally focused on whether past information in oil prices predicts exchange rates by using various versions of Granger‐causality tests or out‐of‐sample forecasting (Bal and Rath, 2015; Baghestani and AbuAl‐Foul, 2019; Baghestani et al ., 2019). A handful of empirical studies, however, have found causality running from exchange rates to oil prices (Sadorsky, 2000; Akram, 2009; Beckmann and Czudaj, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%